An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon. Issue 4 (9th March 2022) - Adams, Colin E.; Chavarie, Louise; Rodger, Jessica R.; Honkanen, Hannele M.; Thambithurai, Davide; Newton, Matthew P.
Abstract: There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap, where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.